Factors associated with carbon tax awareness: a systematic review - Dapari, Rahmat; Baharuddin, Muhammad Zul Aizzat; Abd Ghani, Norfarihah; Ahmad Daud, Arfizah; Mansor, Zawiah Binti; Che Dom, Nazri; Hassan, Mohd Rohaizat; Syed Abdul Rahim, Syed Sharizman; Ahmed Bagubair, Ahmed Awadh (Malaysian Journal of Public Health Medicine, 2024)
Carbon dioxide is the primary greenhouse gas responsible for approximatelythree-quarters of the world’s gas emissions.Carbon dioxide (CO2) is an important heat-trapping gas, or greenhouse gas that comes from the extraction and burning of fossil fuels.Its presence in the atmosphere warms the planet, but the rising concentration of greenhouse gases has led toclimate change due to hotter temperaturesacross the globe.Carbon tax is defined as a fee imposed on the burning of carbon-based fuels,such ascoal, oil,and gas,whichaims to reduce greenhouse gasses. Thus, thisstudy aimedto evaluate the factorsassociated with carbon tax awareness among the general population.This systematic reviewaimed to systematically evaluate factors associated with carbon tax awareness among the general population.A systematic search was conducted in Scopus and ScienceDirect. This review was conducted based onthe Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The literature search was conducted from1stNovember until 1stDecember 2022 using Scopus and ScienceDirect databases. The following keywords were used tosearch for related articles: “carbon tax policy” AND “awareness” AND “factor” OR “factor associated”. All retrieved articles were imported into EndNote20.A total of twostudies met the inclusion and exclusion criteria,with oneeligible article from Taiwanand1 from Canada. The analysed articles were published between 2020 and 2022. The identified associated factorsof carbon tax awareness, namely trust in the federal government, climate change concerns, environmental concerns, education, health consciousness, and age,can be used as a guide fordesigningevidence-based measures and policies that address these concerns.